2002
DOI: 10.1093/emboj/cdf511
|View full text |Cite
|
Sign up to set email alerts
|

Co-localization of centromere activity, proteins and topoisomerase II within a subdomain of the major human X α-satellite array

Abstract: Dissection of human centromeres is dif®cult because of the lack of landmarks within highly repeated DNA. We have systematically manipulated a single human X centromere generating a large series of deletion derivatives, which have been examined at four levels: linear DNA structure; the distribution of constitutive centromere proteins; topoisomerase IIa cleavage activity; and mitotic stability. We have determined that the human X major a-satellite locus, DXZ1, is asymmetrically organized with an active subdomain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
111
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(114 citation statements)
references
References 58 publications
3
111
0
Order By: Relevance
“…Thus, the abnormal cell divisions seen in yeast top2 mutants (Holm et al, 1985;Uemura and Yanagida, 1986), and in vertebrate cells treated with topoII inhibitors (Downes et al, 1991;Ishida et al, 1991Ishida et al, , 1994Haraguchi et al, 2000) are consistent with the unique ability of topoII to resolve the sister chromatids catenations generated when DNA replication forks meet (Wang, 2002). TopoII has been implicated in mammalian centromere function (Floridia et al, 2000;Spence et al, 2002), and it has been suggested that topoII in yeast may play a role in centromeric chromatin structure (Bachant et al, 2002). Further work is required to understand the relationship between any such structural role, topoII-mediated chromatid decatenation, and the role of the cohesin complex (Nasmyth, 2002) in maintaining sister chromatid cohesion until anaphase (Bernard and Allshire, 2002).…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Thus, the abnormal cell divisions seen in yeast top2 mutants (Holm et al, 1985;Uemura and Yanagida, 1986), and in vertebrate cells treated with topoII inhibitors (Downes et al, 1991;Ishida et al, 1991Ishida et al, , 1994Haraguchi et al, 2000) are consistent with the unique ability of topoII to resolve the sister chromatids catenations generated when DNA replication forks meet (Wang, 2002). TopoII has been implicated in mammalian centromere function (Floridia et al, 2000;Spence et al, 2002), and it has been suggested that topoII in yeast may play a role in centromeric chromatin structure (Bachant et al, 2002). Further work is required to understand the relationship between any such structural role, topoII-mediated chromatid decatenation, and the role of the cohesin complex (Nasmyth, 2002) in maintaining sister chromatid cohesion until anaphase (Bernard and Allshire, 2002).…”
mentioning
confidence: 89%
“…What is the nature of such catenations and why do they seem to affect only a subset of chromosomes? Given the persistent association of sister centromeres after chromatid arms have separated (Losada and Hirano, 2001;Bernard and Allshire, 2002), and the known accumulation of topoII␣ protein (Rattner et al, 1996;Sumner, 1996) and topoII activity (Floridia et al, 2000;Andersen et al, 2002;Spence et al, 2002;Agostinho et al, 2004) at centromeres, one may reasonably speculate that centromeric catenations are uniquely resolved by topoII␣ and persist after anaphase onset in topoII␣-depleted cells. In the absence of cohesin-dependent centromeric cohesion, poleward forces might then be sufficient to allow near normal separation of sister kinetochores, at the expense of severe chromosomal distortions and DNA damage, resulting in the dissociation of many, but not all, sister chromosomes.…”
Section: Essential Role For Topoii␣ Activity In Chromosome Segregationmentioning
confidence: 99%
“…25 Multiple rounds of chromosome fragmentation have been used to derive smaller and smaller derivatives from natural chromosomes. We will refer to the molecules obtained by the first procedure as de novo Figure 3 De novo chromosome formation can be obtained by using a DNA mixture containing centromeric DNA (a-satellite), telomeric fragments (optional) and random genomic (optional) transfected into human cultured cells (a).…”
Section: Artificial Chromosomes Can Be Obtained By In Vitro Chromosommentioning
confidence: 99%
“…The adjacent organization of higherorder and monomeric ␣-satellite, as well as the fact that lower primates have only monomeric ␣-satellite at their centromeres (Rosenberg et al 1978;Musich et al 1980;Maio et al 1981;Thayer et al 1981;Alves et al 1994), has led to the hypothesis that higher-order ␣-satellite evolved from ancestral arrays of monomeric ␣-satellite and subsequently transposed to the centromeric regions of all great ape chromosomes (Warburton and Willard 1996;Alexandrov et al 2001;Schueler et al 2001Schueler et al , 2005Kazakov et al 2003). The relatively recent evolution of higherorder ␣-satellite is intriguing because centromere function is associated with higher-order and not monomeric ␣-satellite in the human genome (Harrington et al 1997;Ikeno et al 1998;Schueler et al 2001;Spence et al 2002).Like other tandem satellite families (Brown et al 1972;Southern 1975;Coen et al 1982), ␣-satellite is subject to concerted evolution, exhibiting greater sequence identity within a species than between species (Willard and Waye 1987b). For example, higher-order repeat units from an array on a particular chromosome are more similar to each other than to the orthologous repeats in other species (Jorgensen et al 1987;Durfy and Willard 1990).…”
mentioning
confidence: 99%
“…The adjacent organization of higherorder and monomeric ␣-satellite, as well as the fact that lower primates have only monomeric ␣-satellite at their centromeres (Rosenberg et al 1978;Musich et al 1980;Maio et al 1981;Thayer et al 1981;Alves et al 1994), has led to the hypothesis that higher-order ␣-satellite evolved from ancestral arrays of monomeric ␣-satellite and subsequently transposed to the centromeric regions of all great ape chromosomes (Warburton and Willard 1996;Alexandrov et al 2001;Schueler et al 2001Schueler et al , 2005Kazakov et al 2003). The relatively recent evolution of higherorder ␣-satellite is intriguing because centromere function is associated with higher-order and not monomeric ␣-satellite in the human genome (Harrington et al 1997;Ikeno et al 1998;Schueler et al 2001;Spence et al 2002).…”
mentioning
confidence: 99%